BUSINESS PERCEPTIONS AND BARRIERS HALAL CERTIFICATE PROCESSING IN KUTA-BALI ISLAMIC ECONOMIC PERSPECTIVE - Nggulam Mustaqim, Misbah (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2025)
The purpose of this study was to determine the perceptions of business actors and the obstacles and barriers faced when applying for halal certificates, both before and after the enactment of Law Number 6 of 2023 concerning Job Creation in the perspective of Islamic economics, especially the researcher took the research location in Kuta Village, Kuta District, Badung Regency, Bali Province—seeing that Balinese society can be said to be a pluralistic society that has various religions. This study uses a qualitative research method, namely a type of research that focuses on understanding the naturalistic arrangement or daily life of a particular phenomenon or person, including the context in which the phenomenon being studied is embedded. It can be concluded that the results of this study: first, that the halal certificate processing process is very strict and impractical, second, the existence of Law Number 6 of 2023 concerning Job Creation, provides a breath of fresh air for business actors in the form of a halal certificate valid for life, practical and uncomplicated submission, especially the Halal Product Process Companion is very protective and very helpful for business actors, third, during the halal certificate processing process, business actors face several obstacles and constraints originating from the business actors themselves, the application system, halal auditors, and the fatwa committee.